Comparison of the Impact of an Optimized Ice Cooling Vest and a Paraffin Cooling Vest on Physiological and Perceptual Strain - Mansoor zare; Habibollah dehghan; Saeid yazdanirad; Amir hossein khoshakhlagh (Elsevier, 2019)
Background: Ice cooling vests can cause tissue damage and have no flexibility. Therefore, these two undesirable properties of ice cooling vest were optimized, and the present study was aimed to compare the impact of the optimized ice cooling vest and a commercial paraffin cooling vest on physiological and perceptual strain under controlled conditions. Methods: For optimizing, hydrogel was used to increase the flexibility and a layer of the ethylene vinyl acetate foam was placed into the inside layer of packs to prevent tissue damage. Then, 15 men with an optimized ice cooling vest, with a commercial paraffin cooling vest, and without a cooling vest performed tests including exercise on a treadmill (speed of 2.8 km/hr and slope of %0) under hot (40°C) and dry (40 %) condition for 60 min. The physiological strain index and skin temperature were measured every 5 and 15 minutes, respectively. The heat strain score index and perceptual strain index were also assessed every 15 minutes. Results: The mean values of the physiological and perceptual indices differed significantly between exercise with and without cooling vests (P < 0.05). However, the difference of the mean values of the indices except the value of the skin temperature during the exercises with the commercial paraffin cooling vest and the optimized ice cooling vest was not significant (P > 0.05). Conclusions: The optimized ice cooling vest was as effective as the commercial paraffin cooling vest to control the thermal strain. However, ice has a greater latent heat and less production cost. Keywords: Heat strain, Ice cooling vest, Optimization, Perceptual strain, Physiological strain